Estudio de factibilidad para la implementación de una granja orgánica de producción y comercialización de carne de cerdo (Sus scrofa domestica), cuyes (Cavia porcellus) y gallinas (Gallus gallus domesticus) para las ciudades de Tabacundo y Cayambe-Ecuador - Cobacango Catucuago, María Susana (2012)
In recent years, the consumption of organic food has captivated the interest of producers and consumers primarily due to the tendency of people to know the origin and traceability of what they consume. Thus within the community of San Pablito Agualongo, we conducted the present feasibility study, through which it will offer the residents of the cities of Tabacundo and Cayambe, an organic meat product, based on respect for the animal to it grows naturally, followed by appropriate standards in the handling of meat and get excellent quality products. In conducting the study found that there was market demand for organic beef, pork, chicken and guinea pig which does not provide a large market opportunity.